2019
DOI: 10.1016/j.jot.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of degenerative and radial tears of the meniscus and resultant meniscectomy on the knee joint: a finite element analysis

Abstract: Objective The objective of this study is to investigate the biomechanics on the knee components caused by degenerative and radial meniscal tears and resultant meniscectomy. Methods A detailed finite element model of the knee joint with bones, cartilages, menisci and main ligaments was constructed from a combination of computed tomography and magnetic resonance images. Degenerative and radial tears of both menisci and resultant medial meniscectomy were used and two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 25 publications
(28 reference statements)
6
30
1
Order By: Relevance
“…Previous studies have shown that without the shock absorption by the meniscus, increasing the direct contact area between the femoral condyle cartilage and the tibial plateau leads to elevated stress, which can result in early cartilage degradation and early-onset osteoarthritis 6 . Although the characteristics of cartilage stress and meniscus displacement in the present model only re ect the transient response of the knee joint under compression load induction, previous studies have suggested that higher shear stress may cause early proteolytic degradation of the meniscus matrix and the tension of the articular cartilage may reduce the strength 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that without the shock absorption by the meniscus, increasing the direct contact area between the femoral condyle cartilage and the tibial plateau leads to elevated stress, which can result in early cartilage degradation and early-onset osteoarthritis 6 . Although the characteristics of cartilage stress and meniscus displacement in the present model only re ect the transient response of the knee joint under compression load induction, previous studies have suggested that higher shear stress may cause early proteolytic degradation of the meniscus matrix and the tension of the articular cartilage may reduce the strength 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In-depth understanding of stress transfer in the articular cavity after APM may help to illuminate the biomechanical causes of OA progression [4][5] . Finite element (FE) simulation can provide intuitive graphical results to explain the biomechanics changes after APM 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing meniscal resection may have di culty regaining previous motion abilities [26,27].…”
Section: Construction Of Ppi Network and Hub Genes Analysismentioning
confidence: 99%
“…2 This stress is shown to increase with meniscectomy. 1 Therefore, preserving and repairing a damaged meniscus has become the new standard to achieve better long-term outcomes for the patient. 4 Past techniques for radial meniscus tear repair used single, double, or crossed horizontal mattress sutures.…”
mentioning
confidence: 99%
“…The functions of the menisci are load distribution, shock absorption, and joint stabilization. 1 Loss of function or injury to the meniscus can result in change in contact area and lead to cartilage degeneration. 2 , 3 Radial tears, which occur perpendicular to the deep edge and extend superficially toward the rim, are considered less common but more complex injuries that result in large meniscal extrusion and increased peak compressive and shear stress in both the menisci and cartilage.…”
mentioning
confidence: 99%